Towards an elementary architecture - Eskinazi, Mara Oliveira; Engel, Pedro (Revista Thésis, 2017)
The design teaching in the first year of the architecture courses has a propaedeutic character. That is, it should allow students to develop basic skills and knowledge that will enable them to undertake more complex activities in subsequent stages. In the architecture course of FAU UFRJ, the propaedeutics for the architectural project has been gradually transformed in the last two decades: it moved away from practices historically linked to the Bauhaus tradition of the Study of Form – based on the creation of plastic compositions of abstract character and on the understanding of their effects on perception – and towards the project of architecture and urbanism. This article presents the description of an exercise conceived in the discipline Conception of Architectural Form II, of the second semester of the architecture course in FAU / UFRJ, with the purpose of making explicit the pedagogical agenda of the discipline, which has among its premises the valuation of a so called "elementary architecture", which is based on the synthetism and visual elementarity of the object. The exercise consists of conceiving a project without a defined program, in a narrow urban lot, by means of manipulating an independent structure formed by pillars and beams and based on a modular frame. The focus is on the relationships between form, structure and space. This agenda, besides being a suited tool for teaching and reflecting on the project practice, also aligns itself with more pressing architectural problems in the construction of Brazilian cities. This is because it opens space for reflection on project principles based on the use of basic forms combined in a formal system compatible with the available constructive means, allied to spatial concepts and urban guidelines capable of guiding the occupation of these territories.